High Ambient Temperature Represses Anthocyanin Biosynthesis through Degradation of HY5 - Kim, Sara; Hwang, Geonhee; Lee, Seulgi; Zhu, Jia-Ying; Paik, Inyup; Nguyen, Thom Thi; Kim, Jungmook; Oh, Eunkyoo (Frontiers in Plant Science, 2017)
Anthocyanins are flavonoid compounds that protect plant tissues from many environmental stresses including high light irradiance, freezing temperatures, and pathogen infection. Regulation of anthocyanin biosynthesis is intimately associated with environmental changes to enhance plant survival under stressful environmental conditions. Various factors, such as UV, visible light, cold, osmotic stress, and pathogen infection, can induce anthocyanin biosynthesis. In contrast, high temperatures are known to reduce anthocyanin accumulation in many plant species, even drastically in the skin of fruits such as grape berries and apples. However, the mechanisms by which high temperatures regulate anthocyanin biosynthesis in Arabidopsis thaliana remain largely unknown. Here, we show that high ambient temperatures repress anthocyanin biosynthesis through the E3 ubiquitin ligase CONSTITUTIVE PHOTOMORPHOGENIC1 (COP1) and the positive regulator of anthocyanin biosynthesis ELONGATED HYPOCOTYL5 (HY5). We show that an increase in ambient temperature decreases expression of genes required in both the early and late steps of the anthocyanin biosynthesis pathway in Arabidopsis seedlings. As a result, seedlings grown at a high temperature (28°C) accumulate less anthocyanin pigment than those grown at a low temperature (17°C). We further show that high temperature induces the degradation of the HY5 protein in a COP1 activity-dependent manner. In agreement with this finding, anthocyanin biosynthesis and accumulation do not respond to ambient temperature changes in cop1 and hy5 mutant plants. The degradation of HY5 derepresses the expression of MYBL2, which partially mediates the high temperature repression of anthocyanin biosynthesis. Overall, our study demonstrates that high ambient temperatures repress anthocyanin biosynthesis through a COP1-HY5 signaling module.